An Influence of Motivation, Work Discipline, and Work Environment on Performance Employees of PT Aurora Indah Elektrik - Siti Mutiah Hasibuan; Abdi Setiawan; Muhammad Alfahmi (Sean Institute, 2024)
This research aims to explore the impact of motivation, work discipline and work environment on employee performance at PT Aurora Indah Elektrik. This study involved 48 contract employees as a population with a sample size as large as the population. Data collection was carried out through questionnaires and analyzed using the multiple linear regression method with the help of SPSS 24.0. The results of the analysis show that motivation, work discipline and work environment individually and together have a positive and significant influence on employee performance. The most influential variable is work motivation. In addition, most of the variation in employee performance can be explained by motivation, work discipline, and work environment, while other factors also make significant contributions. In conclusion, the relationship between employee performance and motivation, work discipline and work environment shows a strong correlation.